2021
DOI: 10.1186/s12864-021-07964-w
|View full text |Cite
|
Sign up to set email alerts
|

Non-coding RNA in raw and commercially processed milk and putative targets related to growth and immune-response

Abstract: Background Bovine milk contains extracellular vesicles (EVs) that play a role in cellular communication, acting in either an autocrine, paracrine, or an exocrine manner. The unique properties of the EVs protect the cargo against degradation. We profiled the ncRNAs (non-coding RNA) present in the EVs from seven dairy products - raw whole milk, heat-treated skim milk, homogenized heat-treated skim milk, pasteurized homogenized skim milk, pasteurized heavy whipping cream, sweet cream buttermilk an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Evidence has been presented that epigenetic termination of TNFAIP3 function by miR-125a and miR-125b could strengthen and prolong NF-κB activity, which promotes DLBCL lymphomagenesis [ 442 ]. Shome et al [ 443 ] identified bta-miR-125a as one of the most abundant miRs of commercial milk related to immunological roles that were not affected by pasteurization, homogenization, or heat treatment. The seed sequence of hsa-miR-125a-5p and bta-miR-125a-5p are identical.…”
Section: Exosomal Micrornas In the Pathogenesis Of Dlbclmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence has been presented that epigenetic termination of TNFAIP3 function by miR-125a and miR-125b could strengthen and prolong NF-κB activity, which promotes DLBCL lymphomagenesis [ 442 ]. Shome et al [ 443 ] identified bta-miR-125a as one of the most abundant miRs of commercial milk related to immunological roles that were not affected by pasteurization, homogenization, or heat treatment. The seed sequence of hsa-miR-125a-5p and bta-miR-125a-5p are identical.…”
Section: Exosomal Micrornas In the Pathogenesis Of Dlbclmentioning
confidence: 99%
“…The seed sequence of hsa-miR-125a-5p and bta-miR-125a-5p are identical. The fine-tuning of TNFAIP3 levels mediated by miR-125 expression had a striking impact on K-63 ubiquitination of TRAF2 and RIP1, IκBα degradation, p65 nuclear accumulation, and transcription of NF-κB target genes [ 443 ]. These events defined an antiapoptotic profile compatible with constitutive NF-κB activation and enhanced the fitness of B lymphoma cells.…”
Section: Exosomal Micrornas In the Pathogenesis Of Dlbclmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of milk, another consideration must be made related to the starting material. It is known that industrialisation processes can affect the composition of milk in terms of bioactive molecules in different manners related to the applied procedure [ 30 , 31 ]. A great number of mEV evaluations have been made using raw milk, although its consumption is not allowed in some countries due to hygiene-related problems.…”
Section: Milk-derived Ev Isolation: a Critical Point To Overcomementioning
confidence: 99%
“…1D ). Additionally, a study examining whether the integrity of EVs is affected during the processing of raw milk has also been reported ( Kleinjan et al, 2021 ; Shome et al, 2021 ). A summary of these papers is shown in Table 2 .…”
Section: Uptake and Stability Of Bovine Milk-derived Extracellular Ve...mentioning
confidence: 99%